Effectiveness of Corn Silk Extract As a Natural Insecticide on Aedes aeegypti Mortality with Liquid Electric Method - Meyrita Meyrita; Supriatno Supriatno; Devi Syafrianti (Universitas Syiah Kuala, 2020)
Corn silk is a part of the corn plant that is still considered waste. Corn silk is dominated by flavonoids, tannins, saponins and essential oils, which are compounds that are toxic to insects, so they have the potential to act as natural insecticides. This study aims to determine the concentration and duration of exposure to corn silk extract which is effective against the mortality of Aedes aegypti mosquitoes by using the liquid electric method. The research approach used is quantitative. This type of research is experimental. The research design used was factorial completely randomized design (CRD) with 3 levels of exposure time factor (A) and 5 levels of concentration factor (B) to obtain 15 treatment combinations with 4 replications. The length of exposure during the study was 30 minutes (T1), 60 minutes (T2) and 90 minutes (T3). The concentration factors given were aquadest (P0) as a negative control, the concentration of corn silk extract was 500 g / L (P1), 1,000 g / L (P2), 1,500 g / L (P3) and d-allethrin 0.08 g / L brand HIT (P4) as positive control. The parameters observed were the Aedes aegypti mosquito mortality and the LC50 value. The data were analyzed using Analysis of Variance (ANOVA) then continued with the Honestly Significant Difference test (HSD) and probit regression analysis. The results showed that the highest mortality of Aedes aegypti mosquitoes was found in the combination of T3P3 treatment with exposure time of 90 minutes (T3) and a concentration of 1,500 g / L (P3) with a percentage of 87.5% mortality. The results of the ANOVA test and the LSD test showed that the interaction between the concentration factor (A) and the exposure time factor (B) was significantly different. The results of the probit regression analysis showed that the extract concentration value that caused 50% (LC50) of Aedes aegypti mosquito mortality was 1740 g / L for 30 minutes of exposure, 713.33 g / L for 60 minutes of exposure and 341.34 g / L for 90 minutes exposure. The conclusion of this study is that the combination of T3P3 corn silk extract treatment is effective as a natural insecticide against the mortality of Aedes aegypti mosquitoes using the liquid electric method.